Environmental integration tool approach: Self-determined commitment and the adoption of pro-environmental behaviors - Henin, Vincent; Uglione, Paula (Frontiers in Psychology, 2022)
The integration between economic development and the environment is a central issue in a contemporary global society. The behavioral change of social actors is one of the crucial challenges of this integration. This paper discusses the role of self-determined commitment in the methodological dynamic of the Environmental Integration Tool/EIT Approach and its potential impact on the adoption of pro-environmental behaviors by local economy actors in the Global South. The EIT Approach was developed by Louvain Coopération, the NGO associated with Université Catholique de Louvain (Belgium) as part of its Food and Economic Security Program, which aims to support social actors in productivity and consumption activities in Africa, Andean America and Asia. The EIT Approach is a pragmatic methodology based on a cyclical dynamic of reflection and action that is integrated into two variants: the EIT Program and the EIT Producer. Under the Food and Economic Security Program, the application of the EIT Producer between 2016 and 2020 resulted in 1466 pro-environmental and self-determined commitments by local entrepreneurs leading to the adoption of 906 pro-environmental actions. This is in line with theories and studies that assume intention as an internal variable that influences people's environmental behavior patterns. The EIT Approach encourages self-determined commitments by local economic agents, representing a crucial methodological aspect for generating pro-environmental behavior besides being a relevant methodology for projects engaged to sustainable development.